Understanding Purchase Intention in Online Skincare Markets: The Mediating Role of Electronic Word of Mouth in the Relationship Between Perceived Price and Celebrity Endorsement - Monna Fransisca; Liem Bambang Sugiyanto; Danial Thaib (International Journal Labs, 2026)
This study aims to analyze the influence of perceived price and celebrity endorsement on purchase intention toward Skintific skincare products on the Shopee platform, as well as to examine the mediating role of electronic word of mouth (e-WOM) in this relationship. This research employed a quantitative approach with an explanatory research design. Data were collected through an online questionnaire distributed to 272 consumers in Jakarta using a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (PLS-SEM) with SmartPLS software to test direct and indirect relationships among variables. The results show that perceived price and celebrity endorsement have positive and significant effects on both e-WOM and purchase intention. E-WOM also has a positive and significant effect on purchase intention and acts as a mediating variable that strengthens the influence of perceived price and celebrity endorsement on purchase intention. The mediating effect of e-WOM is found to be stronger in the relationship between perceived price and purchase intention, highlighting the importance of digital consumer communication in online purchasing decisions. This study focuses on consumers in Jakarta and examines only one skincare brand and a single e-commerce platform, which may limit the broader applicability of the findings. Moreover, the data are based on respondents’ perceptions at one point in time, so the results may not fully capture changes in consumer behavior over time.